Enhancing the tensile strength and morphology of Sansevieria trifasciata Laurentii fibers using liquid smoke and microwave treatments: an RSM approach - Muhammad Arsyad Suyuti; Djarot B. Darmadi; Winarto; Putu Hadi Setyarini (Scientific Reports)
Abstract Liquid smoke (LS), an eco-friendly substance, is effective in modifying natural fibers to enhance their mechanical properties, surface morphology, and thermal stability. This study investigates the effects of LS immersion followed by microwave treatment on the tensile strength, surface morphology, and thermal characteristics of Sansevieria trifasciata Laurentii (STL) fibers. Response surface methodology (RSM) with central composite design (CCD) was used to optimize treatment parameters, including LS immersion time, microwave heating temperature, and duration. Mechanical, morphological, structural, and thermal properties were analyzed using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). Optimal treatment conditions: 120 min LS immersion and microwave heating at 40 °C for 30 min. They resulted in a tensile strength of 370.23 MPa, a 37.21% improvement compared to untreated fibers. Treated fibers exhibited enhanced thermal stability, increased crystallinity, and improved surface morphology. These findings demonstrate that LS and microwave treatments effectively enhance STL fibers’ mechanical properties, surface morphology, and thermal stability, positioning them as promising reinforcement materials for sustainable composite applications.